Non-Adherence in Adult Male Patients with Community-Acquired Pneumonia: Relative Forgiveness of Amoxicillin versus Respiratory Fluoroquinolones - Nerea Carral; John C. Lukas; Oskar Estradé; Nerea Jauregizar; Héctor Morillas; Elena Suárez (Antibiotics, 2023)
The consequences of non-adherence to treatment (NAT) on antimicrobial efficacy may depend on drug forgiveness—a property that should account for pharmacokinetics (PK) and pharmacodynamics (PD) as well as interindividual variability. In this simulation study, relative forgiveness (RF) in NAT, defined as the probability of a successful PK/PD target (PTA) attained under perfect adherence compared to imperfect adherence, was evaluated for amoxicillin (AMOX) (oral 1000 mg/8 h) and two respiratory fluoroquinolones—levofloxacin (LFX) (oral 750 mg/24 h) and moxifloxacin (MOX) (oral 400 mg/24 h)—in virtual outpatients with community-acquired pneumonia for S. pneumoniae. Several NAT scenarios (delay in dose intake and a missed dose) were considered. PK characteristics of virtual patients, including variability in creatinine clearance (70–131 mL/min) and S. pneumoniae susceptibility variability associated with geographical location, were simulated in NAT. In this regard, in regions of low MIC delays from 1 h to 7 h or omission of dose ingestion would not have negative consequences on the efficacy of AMOX because of its good RF associated with the AMOX PK and PD properties; RF of LFX 750 mg or MOX 400 mg/24 h regimen vs. AMOX 1000 mg/8 h is one. However, in regions of elevated MIC for S. pneumoniae AMOX loses its RF, LFX and MOX vs. AMOX, showing higher RF (>1) depending on the CLCR of patients. These results illustrate the importance of considering the RF of antimicrobial drugs in NAT and provide a framework for further studying its implications for clinical success rates.